2005
DOI: 10.1097/01.cco.0000174049.14515.8d
|View full text |Cite
|
Sign up to set email alerts
|

Management of locally advanced cervical cancer

Abstract: Continued improvement in understanding the natural history of cervical cancer, the limitations of the current staging system, and these newer therapeutic options will increase the efficacy of chemoradiation and improved the survival of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Concomitant chemotherapy and irradiation is the standard treatment for advanced squamous cell cervical cancer [164,165], but neoadjuvant chemotherapy followed by radical hysterectomy with pelvic lymphadenectomy appears to be an effective therapeutic option for patients with stages Ib 2 -IIb disease [166,167]. TIP regimen is associated with a higher optimal pathologic response rate than the combination of IFO + CDDP, without any statistically significant benefit on overall survival [167].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant chemotherapy and irradiation is the standard treatment for advanced squamous cell cervical cancer [164,165], but neoadjuvant chemotherapy followed by radical hysterectomy with pelvic lymphadenectomy appears to be an effective therapeutic option for patients with stages Ib 2 -IIb disease [166,167]. TIP regimen is associated with a higher optimal pathologic response rate than the combination of IFO + CDDP, without any statistically significant benefit on overall survival [167].…”
Section: Discussionmentioning
confidence: 99%
“…Calpain Inhibitor VI Synergized with Cisplatin-Cisplatin is extensively used in the treatment of cervical cancer (32), is able to up-regulate p53 expression in HPV-transformed cells (33), and promotes p53-mediated apoptosis (34). Calpain inhibitors are being developed to treat a range of diseases (16) including cancer (17), and we have shown that calpain inhibitor VI is able to inhibit the growth of HeLa or Caski cell xenographs in Foxn1 nu mice (supplemental Fig.…”
Section: A Calpain Inhibitor Restored Rb Protein Levels Repressed E6mentioning
confidence: 99%
“…Cisplatin combined with radiotherapy has become the standard treatment for locally advanced cervical cancer and can achieve survival rates of Ͼ70% (32). For women with disseminated, persistent, recurrent, or metastatic disease, few treatment options exist (42).…”
Section: Why Might This Two-step Process For Rb Degradation Havementioning
confidence: 99%
“…La definición de cáncer cérvico uterino localmente avanzado incluye a pacientes con etapa IB2 a IVA (7). La cirugía no es una opción terapéu-tica para pacientes con etapa IIB, III y IV debido a una elevada proporción de márgenes positivos y factores de alto riesgo de recidiva, aumentando la utilización de radioterapia postoperatoria, incrementando la morbilidad asociada al tratamiento.…”
unclassified